(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The role of literature in teaching foreign language is considerably important in maintaining the interest of students. Therefore, it is considered to be a highly effective tool for language teaching. Moreover, there are many experts who believe that for effective foreign language teaching and learning there should be a proper integration between language and literature. Using literature to teach language has several advantages such as contributing to a better linguistic understanding, a development of creative skills, a higher language proficiency, and an authentic model of language use with its rich potential, it also makes an important contribution to literary appreciation (Ramsaran, 1983). The research in the literature indicates many benefits of using literature in foreign language teaching, particularly in improving reading skills. By reading literary texts students get motivated, become familiar with authentic materials, and learn about a variety of cultures. Indeed, literature presents many positive outcomes in teaching all language skills, in particular students reading skill is honed by using different genres of literature. Short story seems to be the most suitable one since it is short, and aims at giving a ‘single effect’, there is usually one plot, a few characters; there is no detailed description of setting. The aim of this article is to indicate the effectiveness of using short story technique in teaching reading skill.